The phase of Theta oscillations modulates successful memory formation at encoding. (16th April 2021) - Cruzat, Josephine; Torralba, Mireia; Ruzzoli, Manuela; Fernández, Alba; Deco, Gustavo; Soto-Faraco, Salvador
Abstract: Several studies have shown that attention and perception can depend upon the phase of ongoing neural oscillations at stimulus onset. Here, we extend this idea to the memory domain. We tested the hypothesis that ongoing fluctuations in neural activity impact memory encoding in two experiments using a picture paired-associates task in order to gauge episodic memory performance. Experiment 1 was behavioural only and capitalized on the principle of phase resetting. We tested if subsequent memory performance fluctuates rhythmically, time-locked to a resetting cue presented before the to-be-remembered pairs at different time intervals. We found an indication that behavioural performance was periodically and selectively modulated at Theta frequency ( 4 Hz). In Experiment 2, we focused on pre-stimulus ongoing activity using scalp EEG while participants performed a paired-associates task. The pre-registered analysis, using large electrode clusters and generic Theta and Alpha spectral ranges, returned null results of the pre-stimulus phase-behaviour correlation. However, as expected from prior literature, we found that variations in stimulus-related Theta-power predicted subsequent memory performance. Therefore, we used this post-stimulus effect in Theta power to guide a post-hoc pre-stimulus phase analysis in terms of scalp and frequency of interest. This analysis returned a correlation between the pre-stimulus Theta phase and subsequent memory. Altogether, these results suggest that pre-stimulus Theta activity at encoding may impact later memory performance. Highlights: Prestimulus neural activity has an impact on episodic memory encoding. Phase reset at encoding modulates performance periodically at theta frequency. EEG Phase before encoding correlates with successful subsequent memory recognition performance.